Pengaruh Variasi Formulasi terhadap Karakteristik Organoleptik Produk Cookies Ampas Minuman Herbal di Perusahaan X: Penelitian - Nurul Kholisah; Nur Rohmah Lufti A’yuni; Siwitri Munambar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia is renowned for its rich diversity of medicinal plants. Company X is one of the companies operating in the processed medicine and herbal products sector, and one of its products is herbal drink A. The production process of herbal drink A has generated 1.4 tons of pomace over the past three years. This can lead to waste management issues. However, this herbal drink pomace has significant potential to be processed into cookies because it still contains active compounds. This research aims to determine consumer preference for herbal drink pomace cookies.This study employed a quantitative descriptive method. Research locations were selected using accidental sampling. The types of data used in this study were primary data and secondary data as supporting information. Based on organoleptic tests, which included aroma, color, texture, taste, and aftertaste, it can be concluded that Formulation 2 showed the highest overall consumer preference with a percentage of 81.08%, outperforming Formulation 1 with 79.76% and Formulation 3 with 71.44%. Formulation 2 is highly recommended for further product development due to its greater market potential based on consumer preferences.